2006
DOI: 10.1007/s11940-006-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and quality of life issues in patients with amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease that usually results in death secondary to respiratory failure. The psychological reaction to the diagnosis of ALS in patient and caregiver has received increasing attention. Reports are highly variable as to the severity of depressive symptoms in patients with ALS. When they exist, depressive symptoms can be managed with pharmacologic interventions. Recognizing cognitive impairment is essential in the management of patients with ALS. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This fact agrees with already published data that found 44-75% of their ALS patients exhibited significant signs and symptoms of depression [24][25][26]. Prevalence of depression was not different between invasively ventilated and non-ventilated patients or between IV and NIV patients, a fact that is coherent with Kübler et al [27].…”
Section: Discussionsupporting
confidence: 92%
“…This fact agrees with already published data that found 44-75% of their ALS patients exhibited significant signs and symptoms of depression [24][25][26]. Prevalence of depression was not different between invasively ventilated and non-ventilated patients or between IV and NIV patients, a fact that is coherent with Kübler et al [27].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, 15% of them had severe depressive symptoms. 48 , 49 Prevalence of depression does not show differences between invasively ventilated and nonventilated patients or between IV and NIV patients. This data is coherent with Kübler et al 50 and Hazenberg et al 51 who indicated that in some patients with ALS, QoL did not improve after 6 months of NIV.…”
Section: Interface For Continuous Nivmentioning
confidence: 98%
“…The occurrence of PBA has been reported in a multitude of neurologic illnesses including, but not limited to, ALS, [15][16][17][18][19] PD and other movement disorders, 13,[20][21][22] MS, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] stroke, [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] various types of dementia and other neurodegenerative disorders, 55-62 traumatic brain injury (TBI), 63-66 central nervous system tumors, [67][68][69][70][71][72][73][74]...…”
Section: Epidemiologymentioning
confidence: 99%